The relationship between leadership and flow: a daily diary study - Simmons, Mathias J. (Kansas State University, 2015)
The current study examines how leaders craft conditions of the workplace to make it more conducive for flow to occur in their followers and what beneficial effects this has on employee well-being and performance. Data from 43 employees surveyed daily over two work weeks suggested that transformational leaders and leader-member exchange relationships impact several workplace conditions that in turn impact flow. Also, daily flow experiences were related to daily psychological well-being and daily performance.
Keywords: Leadership; Flow; Well-being; Performance; Organizational Behavior (0703); Psychology (0621)